Prolonged Extreme Cold Water Diving and the Acute Stress Response During Military Dive Training - Kelly, Karen R.; Arrington, Laura J.; Bernards, Jake R.; Jensen, Andrew E. (Frontiers in Physiology, 2022)
Introduction: Cold water exposure poses a unique physiological challenge to the human body. Normally, water submersion increases activation of parasympathetic tone to induce bradycardia in order to compensate for hemodynamic shifts and reduce oxygen consumption by peripheral tissues. However, elevated stress, such as that which may occur due to prolonged cold exposure, may shift the sympatho-vagal balance towards sympathetic activation which may potentially negate the dive reflex and impact thermoregulation. Objective: To quantify the acute stress response during prolonged extreme cold water diving and to determine the influence of acute stress on thermoregulation. Materials and Methods: Twenty-one (n = 21) subjects tasked with cold water dive training participated. Divers donned standard diving equipment and fully submerged to a depth of ≈20 feet, in a pool chilled to 4°C, for a 9-h training exercise. Pre- and post-training measures included: core and skin temperature; salivary alpha amylase (AA), cortisol (CORT), osteocalcin (OCN), testosterone (TEST) and dehydroepiandosterone (DHEA); body weight; blood glucose, lactate, and ketones. Results: Core, skin, and extremity temperature decreased (p < 0.001) over the 9-h dive; however, core temperature was maintained above the clinical threshold for hypothermia and was not correlated to body size (p = 0.595). There was a significant increase in AA (p < 0.001) and OCN (p = 0.021) and a significant decrease in TEST (p = 0.003) over the duration of the dive. An indirect correlation between changes in cortisol concentrations and changes in foot temperature (ρ = -0.5,p = 0.042) were observed. There was a significant positive correlation between baseline OCN and change in hand temperature (ρ = 0.66, p = 0.044) and significant indirect correlation between changes in OCN concentrations and changes in hand temperature (ρ = -0.59, p = 0.043). Conclusion: These data suggest that long-duration, cold water diving initiates a stress response—as measurable by salivary stress biomarkers—and that peripheral skin temperature decreases over the course of these dives. Cumulatively, these data suggest that there is a relationship between the acute stress response and peripheral thermoregulation.